Cơ sở dữ liệu Chuyên gia khoa học Việt Nam được đào tạo tại Liên minh châu Âu - Tào, Hương Lan (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Briefs the 7th EU Framework Programme on Science and Technology (FP7) and activities pushing up the participation of Vietnam in it; describes the process of creating Database on Vietnamese scientific specialists trained in EU: the way of collecting data, obtained results and practical benefit; sets forth concrete recommendations for maintaining and developing this database.